إشكالية البيان في مرويات النزول القرآني بين الأسباب والأحكام - رحماني, إبراهيم (University of Eloued جامعة الوادي, 2005)
يعالج هذا الموضوع مسألة الروايات الواردة في أسباب النزول القرآني، وما تدلّ عليه من حيث بيانها للسبب في إطار وظيفتها المساعدة لحسن فهم النص القرآني على حقيقته، ومن حيث بيانها للحكم الذي يتضمنه النص القرآني ويستفاد منه في التشريع. ومن خلال بيان اصطلاح الصحابة وكثير ممن جاء بعدهم وتوسعهم في مدلول مصطلح «أسباب النزول»، ثم عرض نماذج مختلفة لمرويات النزول القرآني؛ نخلص إلى أن العبرة بالسياق الذي ورد في إطاره النص، وليس فيما روي على أنه أسباب نزول. This article treats the question of the different narrations mentioned about the causes which made the Coran descend. Moreover, it is about the role of these narrations for a better understanding of the essence of the Coranic Text on one part, and in revealing the verdict contained in the Coranic Text which is made use of in legislation on the other part. Therefore, through exposing the term ‘the cause of descent’ used by the followers and those who came after them whom used it with a wider view, and after showing different examples of narrations about the Coran descent, we come up with the importance of the ‘context’ within which the text appears and not with the term ‘the cause of descent’.
مقال بمجلة البحوث والدراسات
Keywords: مرويات النزول القرآني - أسباب - أحكام